Arquitetando aplicações robustas com gerenciamento de estado front-end no Tribunal de Contas do Estado do Rio Grande do Norte - Maciel, Suzyanne Xavier (2024)
In the context of the Tribunal de Contas do Estado do Rio Grande do Norte (TCE-RN), which is undergoing a technological migration process, this article presents the suggestion of a library that offers centralized state management for Angular applications. Highlighting the importance of Functional Reactive Programming (FRP) in application development, considering the increasing demand for data manipulation today, this paradigm proves to be useful for optimizing the development process, structuring code, standardizing projects, improving maintainability, and enhancing application performance.